EDUCOMUNICAÇÃO, DESENHO ANIMADO E PÚBLICO INFANTIL: Análise e Sugestão para a Alfabetização Midiática na infância - Thayna Rafaela de Oliveira (2021)
The aim of this thesis is to discuss the relationship of Educommunication, cartoons and children's audience in the development of the Media Literacy process in childhood, from the use of the principles of educommunicative practice, through the critical analysis of a media product known by children , in the classroom and mediated by the teacher. The aim is, then, to understand the relationship between teaching, media and children, going through the ways in which human beings obtain knowledge about the world to their interaction and learning with the media, taking into account the mediations, discussed by Martín- Barbero (1997) and Orozco-Gómez (2014). In this context, where Communication and Education are related, the concept of Educommunication and Media Literacy is presented, based on Citelli and Orofino (2014), Ferrari, Machado and Ochs (2020), Buckingham (2012), Kellner and Share (2008 ), Bévort and Belloni (2009), Soares (1999; 2003; 2014), Freire (1985; 2010) and Aparici (2014). The research approaches the history of animation in the world and in Brazil, its characteristics and language, cinema and education, television, children’s and educational programs, and the broadcasting of cartoons on TV. For the practical part of the research, the Brazilian animated television series "Irmão do Jorel" is used as an object of empirical study for the application of a critical media analysis activity, conducted by teachers and students of municipal schools in the city of Campo Grande, using as a research technique the Focal Group qualitative research method. As a result, the research points to the possibility of the principles of Educommunication as effective to initiate the process of Media Literacy in childhood, through the analysis of cartoons, being fundamental the teacher training for a critical perspective on media.